Perception of students about Quality teaching for the Subject of Biology at Secondary School Level - Summayyah Sajid; Jabeen Kausar Kahut; Tahira Noor; Dr. Ghazala Shaheen; Dr. Sajid Rehman , (Dialogue Social Science Review (DSSR), 2025)
x This study was conducted to find perception of students about quality teaching and learning of students in the subject of biology at secondary school level. The objectives of study were: (i) to find the medium of instruction, (ii) to explore different aspects of quality of teaching to the students. There were six groups of participant students of Biology selected through purposive sampling technique from secondary schools of district Rawalpindi. The research was qualitative in nature. In-depth interviews were used as a data collection tool. For analyzing the data thematic analysis was used. Conclusion and recommendations were drawn on the basis of common aspects and theme. The research was beneficial for biology teachers to improve the quality of teaching for motivating students learning. It was concluded that teachers used English, Urdu and Punjabi as a medium of instruction. Students learnt Biology in the class by understanding concepts from teacher through taking notes, in group discussion, elaboration of concept in native language and by focusing diagrams in the text book. All the students perceived that their teachers linked Biology lessons with other subjects like Biophysics, Biochemistry and Bio-economics etc. Students mostly liked practical work, diagrams making and solving exercise questions during the class. Students proposed that teachers can improve the lesson by explanation of concepts with diagrams, models and daily life examples. The study will be significant for teachers to improve the teaching of Biology. In this way the academic performance of the students will also increase.